2022
DOI: 10.1097/sla.0000000000005408
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Renin–Angiotensin System Inhibitors Improve Major Outcomes of Heart Failure Patients Undergoing Cardiac Surgery

Abstract: The aim of this study was to study the association of perioperative administration of renin angiotensin system inhibitors (RASi) and clinical outcomes of patients with heart failure (HF) undergoing cardiac surgery. Summary Background Data: It is controversial whether the perioperative RASi should be administered in HF patients undergoing cardiac surgery. Methods: A total of 2338 patients with HF and undergoing CABG and/ or valve surgeries at multiple hospitals from 2001 to 2015 were identified from STS databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“… 11 More recently, observational studies have demonstrated that pre‐ or perioperative use of renin–angiotensin system inhibitors was associated with a lower risk of 30‐day mortality after CABG surgery. 33 , 34 In the HOPE (Heart Outcomes Prevention Evaluation) trial of patients with vascular disease or diabetes and cardiovascular risk factors, ramipril reduced cardiovascular death, MI, and stroke versus placebo (14% versus 17.8%, relative risk 0.78, 95% CI, 0.70–0.86). 9 Although 26% of patients in the HOPE trial had undergone CABG surgery, results for this subgroup were not reported.…”
Section: Discussionmentioning
confidence: 99%
“… 11 More recently, observational studies have demonstrated that pre‐ or perioperative use of renin–angiotensin system inhibitors was associated with a lower risk of 30‐day mortality after CABG surgery. 33 , 34 In the HOPE (Heart Outcomes Prevention Evaluation) trial of patients with vascular disease or diabetes and cardiovascular risk factors, ramipril reduced cardiovascular death, MI, and stroke versus placebo (14% versus 17.8%, relative risk 0.78, 95% CI, 0.70–0.86). 9 Although 26% of patients in the HOPE trial had undergone CABG surgery, results for this subgroup were not reported.…”
Section: Discussionmentioning
confidence: 99%